Assessing the Shopee Consumer Decision Model - Eni Reptiningsih (Innovation Business Management and Accounting Journal, 2023)
This study seeks to determine the impact of brand awareness, brand loyalty, brand association, and perceived quality, on purchasing decisions made by Shoppes Jawa Barat customers. The non-probability sample method uses purposive sampling, which is based on the criteria of West Java Shoppee users and those who make purchases through the website or mobile application (Android). The research sample is 92 respondents. Analysis using multiple linear regression. The results showed that brand awareness, brand loyalty, brand association, and perceived quality have the greatest influence on customer purchasing decisions. These results indicate that the higher the level of brand awareness, brand association, and perceived quality held by Shopee customers in West Java, the more likely they are to make a purchase decision. However, a unique finding is that perceived quality does not play an important role in efforts to increase purchasing decisions for Shoopee products in West Java. In other words, these variables have an important contribution in shaping customer preferences and purchasing decisions.